Rasio Profitabilitas dan Kinerja Saham - Herbowo; Nanik Niandari; Budhi Purwantoro Jati (Jurnal Penelitian Ekonomi Akuntansi, 2023)
This study aims to test the effect of Return on Equity (ROE), Return on Investment (ROI) and Operating Profit Margin (OPM) on stock performance. This research was conducted on basic industrial and chemical sector manufacturing companies listed on the IDX. 77 companies were used as samples with an observation number of 230 companies. The sampling method used purposive sampling with multiple linear regression analysis. This study used secondary data in the form of company financial statements downloaded through the company's www.idx.co.id and official website. The results showed that only Return on Equity has a positive effect on stock performance while the Return on Investment (ROI) and Operating Profit Margin (OPM) do not affect stock performance. This research is expected to strengthen empirical evidence regarding the influence of profitability factors on an entity's stock returns. This research has limitations, namely that it only tests the influence of fundamental factors in the form of financial profitability ratios, so that further research can involve fundamental factors outside the company's financial performance, such as macroeconomic factors.